Design a Rainwater Harvesting System for a Bungalow House Suitable for Malaysia Environment - idris, ahmad fu'ad; Noor Wira, Megat Saifulnazmi (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Water is one of the most essential natural resources which maintains sustainability in life and environment. Humans, animals, plants or other living creatures could not survive without water because water is one of the basic needs in life. Although Malaysia is blessing with plentiful of rainfall but water being wasted in unproductive way. Due to that, it affects the cost of utility bills which keep increasing in this country and this is the problem which need to be solve. In consequence, the government has introduced the rainwater harvesting system as a preference to reduce the cost and the waste of water. This study was conducted to design a rainwater harvesting system for a bungalow house in Malaysia. Based on monthly rainfall, this RWHS is capable to store 4000 liter per month. In short, Rainwater Harvesting System for Bungalow House in Malaysia is successfully designed.